Interest rate clustering in UK financial services markets - Ashton, John K.; Hudson, Robert S. (Journal of Banking & Finance, 2008)
This study forwards an explanation and empirical investigation of price clustering in retail banking markets. It is proposed that price or interest rate clustering forms in retail markets as firms wish to maximise returns from customers, some of whom have difficulties in recalling and processing price information. This theory is developed and tested using a dataset of retail interest rates from the UK which enables interest rate clustering to be viewed in both lending and investment markets, and at different levels of financial involvement. It is found that interest rate clustering occurs in a manner consistent with firms maximising returns from customers. These findings are viewed to be a key policy concern for financial regulators and firms concerned with consumer protection.